2022
DOI: 10.3390/met12122002
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Metal in the Catalytic Reactions of Hydrogenation–Dehydrogenation of Polycyclic Hydrocarbons for Hydrogen Storage

Abstract: The design of benign and safe hydrogen storage systems is the priority in the development of new energy carriers. The storage of hydrogen in a liquid or compressed state, as well as in metal hydrides and adsorbents, depends on pressure and temperature and under normal conditions does not meet the criteria of the target hydrogen storage capacity, energy consumption for hydrogen storage or safety. The storage of hydrogen in chemical compounds in which it is naturally included in the composition is the only alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Table 2 describes that using the Fe-Co/ZSM-5, the degradation products consist mostly of 2-ethylbiphenyl, which is probably a source of phenanthrene formation. The probable mechanism of anthracene hydrogenation with obtained catalysts is as follows (Scheme 1): Table 3 compares values of anthracene conversions and yields of dihydroanthracene, tetrahydroanthracene and octahydroanthracene during anthracene hydrogenation with catalysts of platinum and rhodium added on Al2O3 [36] with the obtained values in this study. Table 3 compares values of anthracene conversions and yields of dihydroanthracene, tetrahydroanthracene and octahydroanthracene during anthracene hydrogenation with catalysts of platinum and rhodium added on Al 2 O 3 [36] with the obtained values in this study.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Table 2 describes that using the Fe-Co/ZSM-5, the degradation products consist mostly of 2-ethylbiphenyl, which is probably a source of phenanthrene formation. The probable mechanism of anthracene hydrogenation with obtained catalysts is as follows (Scheme 1): Table 3 compares values of anthracene conversions and yields of dihydroanthracene, tetrahydroanthracene and octahydroanthracene during anthracene hydrogenation with catalysts of platinum and rhodium added on Al2O3 [36] with the obtained values in this study. Table 3 compares values of anthracene conversions and yields of dihydroanthracene, tetrahydroanthracene and octahydroanthracene during anthracene hydrogenation with catalysts of platinum and rhodium added on Al 2 O 3 [36] with the obtained values in this study.…”
Section: Resultsmentioning
confidence: 58%
“…The probable mechanism of anthracene hydrogenation with obtained catalysts is as follows (Scheme 1): Table 3 compares values of anthracene conversions and yields of dihydroanthracene, tetrahydroanthracene and octahydroanthracene during anthracene hydrogenation with catalysts of platinum and rhodium added on Al2O3 [36] with the obtained values in this study. Table 3 compares values of anthracene conversions and yields of dihydroanthracene, tetrahydroanthracene and octahydroanthracene during anthracene hydrogenation with catalysts of platinum and rhodium added on Al 2 O 3 [36] with the obtained values in this study. Table 3 demonstrates that the catalysts obtained in this study are inferior to catalysts of platinum and rhodium in total anthracene conversion and octahydroanthracene yield.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Since hydrogenation enthalpy is below 62.7 kJ/mol it is expected that the temperature for dehydrogenation can be decreased. This involves that condensed polycyclic compounds are advantageous since the heat of the reaction decreases with the higher number of aromatic rings (Kustov and Kalenchuk 2002). For example, the dehydrogenation temperature can be lowered by lowering the pressure or applying separation techniques within the reactor (or between catalyst beds) (Müller et al 2021).…”
Section: Lohc Systems/compoundsmentioning
confidence: 99%
“…The observation of a high amount of cisdecalin showed that hexahydronaphthalene was hydrogenated to 9,10-octalin, not to 1,9octalin and then, it isomerized to 1,9-octalin which further be hydrogenated to cis-and trans-decalin. In addition, the adsorption of naphthalene occurred at one active metal, so naphthalene hydrogenation was structure-insensitive [8] but the adsorption of tetralin formed during the hydrogenation of naphthalene, as depicted in the mechanism by Rautanen et.al. (2002), needed an ensemble of atoms of the active metal and its hydrogenation was structure-sensitive.…”
Section: Introductionmentioning
confidence: 99%